Oral history in the classroom: Clarifying the context through historical understanding (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The focus of this paper is on the use of oral history in the classroom and it aims to suggest a method in which oral history recordings and transcriptions may be used to enhance historical understanding among learners by making historical context clear. Firstly, the paper gives background information on the historical research which was largely based on the oral testimony of World War Two veterans and former prisoners-of-war. This theme serves as an example theme for history lessons in especially the Senior Phase classroom as preparation for the FET-phase classroom. Secondly the paper looks at ways in which these sources can be used in the classroom. By using oral sources it is hoped that learners and teachers may move beyond the so-called “hard” forms of historical knowledge, in other words the facts or content knowledge and gain insight into historical significance through the context which oral sources are able to uncover. The paper concludes with ideas and example questions on how students’ interest in the past can be enhanced as they confront oral testimony, thereby increasing their appreciation for the past as well as their respect for those who experienced the historical events first hand. The use of oral history in the classroom reveals students’ misunderstandings of the past and may help educators to address the specific problems of comprehension.Several examples of such cases are mentioned in the paper, including instances where linguistic skills and critical thinking skills may be potentially improved. Apart from creating awareness of historical context, the use of oral testimony has the potential to broaden vocabulary and develop students’ critical thinking skills when, through oral history, they investigate issues of historical accuracy, diverse perspectives and employ the research skills historians regularly use, including communication, analysis and evaluation.
Keywords: Senior Phase history; Further Education and Training (FET) phase history; Oral History; Historical Context; Historical Skills; Primary Sources; Prisoners-of-War